2022
DOI: 10.54204/tmji/vol412022005
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth In The Stability Of The Nation With Taxes And The Important Role Of Foreign Direct Investment

Abstract: This study investigates economic growth, taxes and foreign direct investment. This study investigates data from the 2000 to 2020 starting point to generate “autoregressive vectors” that can be used to determine relationships between variables. This model is used to analyze foreign direct investment, economic growth and taxes in Indonesia using secondary data from the World Bank. We find that The role of taxes in improving economic stability in Indonesia is very important and has a fairly high interrelationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…They claim that the threshold is 90% of the debt to GDP ratio. However, this study has been criticized for methodological and computational errors [12] Another study using panel data is Asteriou, Pilbeam, & Pratiwi [13], who find that there is a negative relationship between initial public debt and subsequent economic growth, with a smaller effect in developed countries. They also found that there is a nonlinear threshold around 85% of the debt-to-GDP ratio.…”
Section: Ease Of Usementioning
confidence: 96%
“…They claim that the threshold is 90% of the debt to GDP ratio. However, this study has been criticized for methodological and computational errors [12] Another study using panel data is Asteriou, Pilbeam, & Pratiwi [13], who find that there is a negative relationship between initial public debt and subsequent economic growth, with a smaller effect in developed countries. They also found that there is a nonlinear threshold around 85% of the debt-to-GDP ratio.…”
Section: Ease Of Usementioning
confidence: 96%